QUALITY OF FINANCIAL INFORMATION MANAGEMENT SYSTEM ON QUALITY OF FINANCIAL STATEMENTS OF LOCAL GOVERNMENT - Sri Dewi Anggadini (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2018)
This research have respondents taken in this study users of financial information systems management application area at the Finance Department in all units of Bandung City Local Devices as much as 67 units of the Work Unit of the Region. Questionnaires were distributed as many as 67 questionnaires. Questionnaires are returned 67 and included in data processing. The method used in this research is descriptive and verifikatif with quantitative approach. Sources of data in this study is primary data with data collection techniques conducted by survey method using questionnaires. The analysis method used in this research is Structural Equation Modeling (SEM) through Partial Least Square (PLS) approach using SmartPLS 3.0 software. The results of this study indicate that Quality Management Information Systems Local Finance on the quality of local government financial statements of 46.63%.